International Stock Market Diversification: A Co-integration Analysis of BRICS and Pakistan - Zahid, Waleed (2019)
This study explores the possible opportunities for international stock market diversification amongst Pakistan, Brazil, Russia, India, China and South Africa. Due to increased globalization the emerging markets are a preferred source of investment across the globe. In order to assess international stock market diversification opportunities within the emerging markets short- and long-term relationships amongst Pakistan and BRICS are examined. The time period for the data collected under this research is from July 01, 2000 till June 30, 2019 divided in two groups. The cointegration test of Johansen (1988) has been employed to examine the long-term relationship whereas the Granger Causality (1969) method is applied to measure the short-term relationship. The results from the Johansen cointegration test identify the opportunities for Pakistani investors for international stock market diversification amongst the BRICS countries. Furthermore, the results also find conclusive evidence regarding diversification opportunities available for BRICS countries amongst each other. The Granger Causality tests help us to identify any presence of short-term relationships amongst the sample of countries. The results show that Pakistani investors have many opportunities for short term diversification. Moreover, most of the BRICS countries do not have a short-term relationship amongst each other giving an opportunity for short term international portfolio diversification within the trading bloc. The results from this study will be useful for the investors who domicile in Pakistan and BRICS countries while constructing their stock portfolios. Findings from this study will help them merge funds accordingly from the selected markets which will eventually lead to a portfolio with increased risk return performance as compared to a portfolio consisting of only native stocks.